2018
DOI: 10.1027/0269-8803/a000180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative and Psychophysiological Responses to Short Film Clips of Different Emotional Content

Abstract: Abstract. The study presents self-report and psychophysiological data obtained in response to short film clips representing scenes related to different emotions. This was done in order to obtain evidence on the structure of positive and negative affective states following a combined dimensional/categorical approach to emotion and based on responses to stimuli that are more realistic than the static pictures usually employed in the study of emotion. Affective ratings and self-report measures showed a differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…increases in arousal. Consistent with these previous studies (Aguado, Fernández-Cahill, Román, Blanco, & Echegaray, 2016;Irrazabal et al, 2015;Moltó et al, 2013;Zupan & Babbage, 2016), the boomerang placed neutral fi lm clips in a neutral and calm center, and the rest of the clips were distributed at the poles. The negative pole (anger, disgust, fear, and sadness) has more arousal than the positive pole (amusement and tenderness).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…increases in arousal. Consistent with these previous studies (Aguado, Fernández-Cahill, Román, Blanco, & Echegaray, 2016;Irrazabal et al, 2015;Moltó et al, 2013;Zupan & Babbage, 2016), the boomerang placed neutral fi lm clips in a neutral and calm center, and the rest of the clips were distributed at the poles. The negative pole (anger, disgust, fear, and sadness) has more arousal than the positive pole (amusement and tenderness).…”
supporting
confidence: 78%
“…The LATEMO-E set of fi lm clips includes both intense and discrete stimuli. Extensive evidence shows the existence of specifi c patterns of responses in subjective emotional reports and central and peripheral nervous system activity in response to specifi c emotions (Aguado et al, 2016). Several studies have shown that the impact of each discrete emotion on cognition, together with other factors (e.g., age and sex), emotional experience (Bradley & Lang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…First, although our data indicate alterations of ANS‐activity following erotic and aversive cues (Wang et al, 2018), we did not directly assess subjective arousal. However, psychophysiological ANS‐measures and subjective measures tend to co‐vary (Aguado et al, 2018; Lang et al, 1990). Moreover, pupil dilation during mental imagery covaries with subjective arousal (Henderson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First, although our data indicate alterations of ANS-activity following erotic and aversive cues (Wang et al, 2018), we did not directly assess subjective arousal. However, psychophysiological ANS-measures and subjective measures tend to co-vary (Aguado et al, 2018; Lang et al, 1990). Moreover, pupil dilation during mental imagery covaries with subjective arousal (Henderson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%